Boundary Spanning Roles in Communities & Organizations: Implications for Adult Educators - Jenny W. Jordan; Katherine Rose Adams; Casey D. Mull (Adult Education Research Conference, 2013)
As adult educators, we work across communities, programs, and organizations. We serve as, work with, and build capacity of boundary spanners. Our collaborations connect people across boundaries and convince others to work together for a common goal. This manuscript explores boundary spanners in three contexts: community partners, contractors, and volunteers.